Pengembangan Media Pembelajaran Mit App Inventor Dalam Meningkatkan Pemahaman Siswa Pada Mata Pelajaran Geografi - Fitri Rahma Widia; Momon Dt Tanamir; Nila Afryansih (Departement of Mathematics Education, 2023)
This study aims to find out and analyze the development, feasibility and practicality of developing learning media mit app inventor learning media in increasing students' understanding of geography subjects. The type of research used in this study is research and development (Research and Development). The 4D model includes 4 stages, namely: Define, Design, Development, Desiminate. The subjects in this study were students of class XI IPS 1 and class XI IPS 3 who took part in the geography learning process at SMAN 1 Linggo Sari Baganti for the 2023/2024 academic year, namely 58 students. The results of the study found that: 1) The development of learning media for this inventor includesvalidation from experts, namely media experts, education experts, language experts and IT experts so that media validation data is obtained and then processed with the Interaclass Coefficient Correlation (ICC) formula assisted by processing using an application SPSS version 22 for Windows, the result is 0.868. if the value is more than 0.5, it can be concluded that the validation level is adequate. 2) Inventor's mit app learning media was declared very feasible after analyzing data processing using Microsoft Excel so that a total score of 277 was obtained with a mean level of 4.85 and a percentage level of 97% with the title